A novel approach to perioperative risk assessment for patients with pulmonary hypertension. Issue 3 (19th July 2021) - Hassan, Hussein J.; Housten, Traci; Balasubramanian, Aparna; Simpson, Catherine E.; Damico, Rachel L.; Mathai, Stephen C.; Hassoun, Paul M.; Steppan, Jochen; Leary, Peter J.; Kolb, Todd M.
Rationale: Pulmonary hypertension (PH) is associated with significant perioperative morbidity and mortality. We hypothesised that pulmonary arterial hypertension (PAH) composite risk assessment scores could estimate perioperative risk for PH patients when adjusted for inherent procedural risk. Methods: We identified patients in the Johns Hopkins PH Center Registry that had noncardiac surgery (including endoscopies) between September 2015 and January 2020. We collected information on preoperative patient-level and procedural variables and used logistic regression to evaluate associations with a composite outcome of death within 30 days or serious postoperative complication. We generated composite patient-level risk assessment scores for each subject and used logistic regression to estimate the association with adverse surgical outcomes. We adjusted multivariable models for inherent procedural risk of major cardiovascular events and used these models to generate a numerical PH perioperative risk (PHPR) score. Results: Among 150 subjects, 19 (12.7%) reached the primary outcome, including 7 deaths (4.7%). Individual patient-level and procedural variables were associated with the primary outcome (all p<0.05). A composite patient-level risk assessment score built on three noninvasive parameters was strongly associated with reduced risk for poor outcomes (OR=0.4, p=0.03). This association was strengthened after adjusting the model for procedural risk. A PHPR score derived from the multivariable model stratified patients into low (0%), intermediate (≤10%), or high (>10%) risk of reaching the primary outcome. Conclusion: Composite PAH risk assessment scores can predict perioperative risk for PH patients after accounting for inherent procedural risk. Validation of the PHPR score in a multicentre, prospective cohort is warranted. For patients with pulmonary hypertension undergoing noncardiac surgery, perioperative risk can be estimated using a model that combines inherent procedural risk with composite PAH risk assessment scores https://bit.ly/3uTCibP